Scent marking by male caribou: an experimental test of rubbing behavior - Adams, Craig A.; Bowyer, R. Terry; Rowell, Jan E.; Hauer, William E.; Jenks, Jonathan A. (Rangifer, 2001)
We studied scent marking by adult male caribou (Rangifer tarandus) during rut in September 1998 at the Large Animal Research Station in Fairbanks, Alaska, USA. We used an experimental approach involving two captive groups of two males each to test for effects of social status, tree size, texture, and scent on rubbing behavior by caribou. Dominant males did not rub more often or for a longer duration than subordinates. Caribou rubbed trees with smaller diameters more often than large-diameter trees. Males preferred trees with bark for rubbing to those trees with their bark removed prior to the experiment. Caribou exhibited no preference for posts with pine-oil applied compared with posts without that aromatic scent. We hypothesize that rubbing of trees by male caribou is related to synchronization or priming of estrus in females, but more research is needed to test that potential function of scent marking.